DMF-Activated Nrf2 Ameliorates Palmitic Acid Toxicity While Potentiates Ferroptosis Mediated Cell Death: Protective Role of the NO-Donor S-Nitroso-N-Acetylcysteine - Diana Abu-Halaka; Adi Shpaizer; Haim Zeigerman; Joseph Kanner; Oren Tirosh (MDPI AG, 2023)
Nonalcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease that can develop into an aggressive form called nonalcoholic steatohepatitis (NASH), which ultimately progresses to cirrhosis, hepatocellular carcinoma (HCC), and end-stage liver failure. Currently, the deterioration of NAFLD is attributed to specific lipid toxicity which could be due to lipotoxicity and/or ferroptosis. In the current study, we evaluated the involvement of the nuclear factor erythroid 2 (NFE2)-related factor 2 (Nrf-2), which is a main activator of phase II metabolism in the two types of lipid-induced toxicity in hepatocytes, lipotoxicity by saturated fatty acids, and in ferroptosis, and the effect of NO donor treatment. AML12 cells were exposed to 600 μM palmitic acid to induce lipotoxicity or treated with 20 μM erastin or 5 μM RSL3 for ferroptosis. In SFA-lipotoxicity, pretreatment with the Nrf2 activator dimethyl fumarate (DMF) managed to ameliorate the cells and the oxidative stress level while aggravating ferroptosis due to emptying the thiol pool. On the other hand, the nitric oxide (NO)-donor, S-nitroso-N-acetylcysteine (NAC-SNO) proved to be effective in the prevention of hepatocytes ferroptosis.